Instructional Leadership Of The Principal In Learning At Eben Haezer 1 Christian Junior High School In Manado City - Meyske Wongkar, Meytha; Sony Junus Lengkong, Jeffry; Junior Mongdong, Romi (International Journal of Educational Research & Social Sciences, 2025)
This study aims to describe the instructional leadership of the principal and to identify the determining factors of such leadership at SMP Kristen Eben Haezer 1 in Manado City. Employing a qualitative approach with a case study design, data were collected through in-depth interviews, direct observations within the school environment, and document analysis. The data were analyzed thematically using an inductive approach. The findings reveal that the principal exercises instructional leadership in a proactive and participative manner. Beyond administrative duties, the principal is actively involved in lesson planning, classroom observation, and professional development of teachers through supervision, training, and mentoring. Christian values serve as the foundation for decision-making and the development of school culture, fostering strong character among all school members. Several factors contribute to the effectiveness of the principal’s instructional leadership, including a clear school vision and mission, strong support from the management team and teachers, open and communicative relationships, and leadership based on personal example. Organizational stability and systematic role distribution also contribute to creating a conducive and high-quality learning environment. This study provides a concrete example of how value-based instructional leadership can be effectively implemented in schools. The findings are significant for school leaders seeking to strengthen their instructional leadership practices and enhance the overall quality of education through collaborative, value-driven approaches.